PENGARUH PROMOSI PENJUALAN, VISUAL MERCHANDISING, ATMOSFER GERAI TERHADAP PEMBELIAN IMPULSIF DI MATAHARI DUTA PLAZA DENPASAR - Dewi, Ni Putu Ayu Sri Kusuma; Jatra, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
Impulsive buying is a behavior that is consumer buying behavior that is formed before entering a store and is carried out unplanned beforehand. The factors that can be considered by the company in the event of impulsive buying to increase sales are sales promotion, visual merchandising, outlet atmosphere towards impulsive purchases at Matahari Duta Plaza Denpasar. The sample size used was 108 respondents of Matahari Duta Plaza Denpasar customers with a purposive sampling technique. Data collection was carried out by distributing questionnaires through Google Forms. The data analysis technique used is multiple linear regression analysis. Based on the research results that (1) sales promotion has a positive and significant effect on impussive buying (2) visual merchandising has a positive and significant effect on impussive buying (3) store atmosphere has a positive and significant effect on impussive buying. Based on these results, it is concluded that sales promotion, visual merchandising, good outlet atmosphere will influence the impulsive buying behavior of Matahari Duta Plaza Denpasar customers.